TERMINAL FLOWER 1 and TERMINAL FLOWER 1d respond to temperature and photoperiod signals to inhibit determinate growth in cucumber. (9th June 2021) - Wen, Haifan; Pan, Jian; Chen, Yue; Chen, Guanqun; Du, Hui; Zhang, Leyu; Zhang, Keyan; He, Huanle; Wang, Gang; Cai, Run; Pan, Junsong
Abstract: Plants monitor environmental cues to balance their vegetative and productive growth by optimizing their inflorescence architecture. TERMINAL FLOWER 1 (TFL1) and its orthologs regulate the inflorescence structure in cucumber, yet the mechanisms underlying their responses to environmental factors and the formation of terminal flowers remain elusive. Here, we performed map‐based cloning to identify the gene that controls a season‐dependent determinate growth phenotype and found that it was caused by the complete deletion of CsTFL1 in the genome of cucumber line WI1983Hde . In the CsTFL1 deletion plants ( CsTFL1 del ), determinate growth could be partially rescued by high‐temperature and long‐day conditions. The expressions of CsTFL1 and its ortholog CsTFL1d could be upregulated by long‐day and high‐temperature signals. Knockdown of CsTFL1d resulted in determinate growth and the formation of terminal flowers in WT. These results indicate that the induction of CsTFL1d expression by long‐day and high‐temperature might partially rescue determinate growth of CsTFL1 del . Furthermore, biochemical analyses showed that CsTFL1d interacts directly with CsNOT2a, which indicated that CsTFL1d and CsTFL1 function via similar regulatory mechanism. Our data suggest that CsTFL1 and CsTFL1d co‐contribute to inhibit determinate growth by responding to temperature and photoperiod signals. It provides mechanistic insights into how environmental cues sculpt the inflorescence architecture of cucumber. Abstract : We performed investigation and analysis on a season‐dependent determinate growth phenotype in cucumber. We used map‐based cloning, qRT‐PCR, transgenic cucumber plants and biochemical experiments to demonstrate TFL1 orthologues, CsTFL1 and CsTFL1d, co‐function in inhibiting cucumber determinate growth by responding to environmental cues. The main point of significance and novelty is the induced expression pattern of CsTFL1 and CsTFL1d according to the seasonal environment change in the greenhouse. By monitoring the phenotype and gene expression for 4 years (2017‐2020), we demonstrate that CsTFL1 and CsTFL1d expressed at a low level in early planted cucumber and then gradually increased from spring to late summer. Downregulated the expression of either of them leads to the determinate growth phenotype with terminal flowers. Moreover, we found that the induction of CsTFL1d expression by long‐day and high temperature condition might partially rescue the loss of function of CsTFL1 plants exhibiting mild determinate growth. To summarize, our results suggest that the expression of CsTFL1 and CsTFL1d maintains the indeterminate growth via balance the vegetative and reproductive development, providing mechanistic insights into how environmental cues sculpt the plant architecture in cucumber.